2020
DOI: 10.5194/essd-2020-211
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Database of Petrophysical Properties of the Mid-German Crystalline High

Abstract: Abstract. Petrophysical properties are a key element for reservoir characterization but also for interpreting the results of various geophysical exploration methods or geophysical well logs. Furthermore, petrophysical properties are commonly used to populate numerical models and are often critically governing the model results. Despite the common need of detailed petrophysical properties, data is still very scarce and often not available for the area of interest. Furthermore, both the online research for publi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…In comparison, the less suitable mafic and metamorphic rocks occupy a rather subordinate area. Additionally, Weinert et al (2020a) found a direct relationship between bulk density and thermal conductivity for the rock samples of the MGCH. The petrophysical models can therefore be used to infer the spatial distribution of thermal properties in the basement, allowing again more realistic potential estimates and heat flow simulations.…”
Section: Basement Structure and Compositionmentioning
confidence: 87%
See 2 more Smart Citations
“…In comparison, the less suitable mafic and metamorphic rocks occupy a rather subordinate area. Additionally, Weinert et al (2020a) found a direct relationship between bulk density and thermal conductivity for the rock samples of the MGCH. The petrophysical models can therefore be used to infer the spatial distribution of thermal properties in the basement, allowing again more realistic potential estimates and heat flow simulations.…”
Section: Basement Structure and Compositionmentioning
confidence: 87%
“…While the highest values are measured in granites due to the increased concentration of radioactive elements, the heat production of mafic rocks is on average almost one magnitude smaller (Vilà et al, 2010). Likewise, the thermal conductivity of granites is by a factor of 1.3 higher than in gabbros (Weinert et al, 2020a). In addition, also the hydraulic conductivity of the basement is strongly influenced by the lithology.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…2c). Petrophysical data, mainly the specific heat capacity, were adapted from the databases of Ba ¨r et al (2020) and Weinert et al (2020). Information on the 3D stress tensor in the Northern URG, provided by Ahlers et al (2021), was used to determine the reactivation potential of fault zones (see details below).…”
Section: D Model and Parametrizationmentioning
confidence: 99%
“…the approach of Oda (1985). The undisturbed rock matrix is considered impermeable (Jing and Stephansson, 2007;Weinert et al, 2020), implying that fluid flow occurs exclusively through connected fractures. The directional permeability is related to the size, orientation, opening and connectivity of the fractures.…”
Section: Dfn Modellingmentioning
confidence: 99%